Combining Intelligent Tutoring Systems and Collaborative Environments with Online Labs - Cordeiro, Raúl (2015)
This chapter discusses the issues of combining intelligent tutoring systems and collaborative environments with online labs. The scenario envisaged mimics the situation present in hands- onlaboratories where students typically work in groups (i.e. they collaborate among themselves in order to complete an experiment) and are supported by a tutor who is physically present during the lab session. Providing these conditions in situations where students perform the experiments in an online lab (virtual, remote, or hybrid) is the key aspect discussed in this chapter, namely in terms of: (1) existing examples reported in the literature, (2) main technical and pedagogical conditions associated with each combined element, and, finally, (3) challenges and benefits of combining both elements with online labs, proposing a new kind of interaction with online labs that will be essential to create the "image” of an “intelligent online tutor and adviser”.